Effect of mHealth based intervention on Maternal Knowledge and Practices of Child Care: A quasi-experimental study - Siswati, Tri Siswati; Sitasari, Almira; Paramashanti, Bunga Astria; Tjaronosari, Tjaronosari; Nurhidayat, Nurhidayat; Wijanarka, Agus; Waris, Lukman (YCAB Publisher, 2024)
Background:Child malnutrition contributes to elevated rates of mortality and morbidity, profoundly affecting child welfare. Maternal childcare knowledge and practices play a pivotal role in addressing this issue. Objective:This study aims to evaluate the impact of the mHealth App on maternal knowledge and practices in child care. Method:A randomized controlled trial was conducted in Yogyakarta, Indonesia, from May to August 2022. Mother-child pairs were assigned to either the intervention (n=100) or control (n=100) groups. Data on maternal knowledge and practices were collected at baseline, follow-up 1, and follow-up 2. Maternal knowledge was assessed using a structured questionnaire covering child growth and development, while feeding practices were evaluated using a yes-no checklist. The analysis of maternal knowledge and practices involved mean difference, t-test, and general estimating equations in STATA-15. Result:The results revealed a consistent increase in knowledge and practice scores between follow-ups 1 and 2. The mHealth application significantly enhanced maternal knowledge about child growth, development, and feeding at follow-up 2 compared to baseline, with improvements of 1.42 (CI 95% 1.34-1.89), 1.32 (CI 95% 1.22-1.72), and 1.45 (CI 95% 1.34-2.42), respectively. Additionally, growth and development monitoring practices increased by 0.80 (CI 95% 0.08-0.99) and 0.98 (CI 95% 0.21-0.99). Conclusion:The mHealth application significantly enhances maternal knowledge and practices related to child growth, development, and feeding. Key words: mHealth; maternal; knowledge; practices; children